TECHNOLOGY AND COGNITIVE SKILLS: INTEGRATING MODERN EDUCATION TO CREATE A GENERATION OF CRITICAL THINKERS - Husna Amin; Ismaul Fitroh; Rita Hayati (Adisam Publisher, 2025)
In today's digital age, technology integration in education has significant potential to develop students' cognitive skills and shape a generation of critical thinkers. The use of innovative educational tools and applications can stimulate analytical thinking, problem-solving and creativity. Technology offers a range of interactive tools that can be customised to students' skill levels, allowing for more individualised and effective learning. However, the application of technology in education also presents challenges that need to be overcome. Issues such as disparities in access to technology, varying digital skills among teachers, as well as the disruption that technology use can cause in the classroom, necessitate appropriate strategies and policies. Inclusive programmes that provide equitable access to tools and training, as well as improving teacher competencies through continuous training, are important steps to overcome these barriers. Ultimately, the successful integration of technology in education depends not only on the availability of technological devices, but also on how they are used to transform teaching and learning methods. A comprehensive approach involving active and collaborative learning, and a focus on developing critical and creative thinking skills, will create a more dynamic and empowering learning environment for students. As such, technology can be a major catalyst in the effort to create a generation ready to face future challenges with superior cognitive skills.